Geomorphology of a recently deglaciated high mountain area in Eastern Anatolia (Turkey) - Azzoni R. S.; Bollati I. M.; Pelfini M.; Sarikaya M. A.; Zerboni A. (Journal of Maps, 2022)
We present a geomorphological map of the Cilo Mountain range located in southeast Turkey that illustrates the recent evolution of the second-most glacierized area of Turkey. The map was produced by the manual delineating of landforms from highresolution satellite imagery (Pleiades and Google EarthTM images). Cilo Mountain glaciation played a crucial role in the evolution of the local physical landscape and even today glaciers are significant features. After the termination of Little Ice Age, deglaciation promoted the onset of multiple and intense surface processes; widespread slope instabilities, due to permafrost melting and frost weathering processes, are still the most active processes. Such processes are further promoted by the scarcity of vegetation. The occurrence of several proglacial lakes significantly contributes to the reduction of sediment output from glaciated watersheds, influencing the evolution of proglacial plains and resulting in a variety of landforms that we identified and described in this work.